Paciente femenino de 54 años con tuberculosis pulmonar. - García Vásquez, Damián Felipe (2021)
A 54-year-old female patient went to the health center due to complications in her health with 2 months of evolution, indicating that she had a general malaise accompanied by night fever, weight loss, and productive cough with phlegm. When performing the physical examination, we observed dyspneic faces, she was oriented and consciously collaborated with all the questions asked, in the cardiopulmonary auscultation no murmurs were heard and it was rhythmic, she also presented vesicular murmur. Tuberculosis is a serious bacterial disease that can be fatal, its transmission mechanism occurs when the affected person coughs or sneezes, most people with this disease do not have symptoms, and when they present they are expectorated with blood, weight loss, night sweats, and fever. Pulmonary tuberculosis is a disease that occurs worldwide, but in tropical countries with low economic resources such as Ecuador it is especially important to know it since the rate of this is very high, due to the different factors that make the mortality of this disease be elevated.